One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species - Zhang, He; Jäger, Peter; Liu, Jie (Zootaxa, 2017)
One new species group of the genus Pseudopoda Jäger, 2000 is described from Yunnan Province, China. The Pseudopoda daliensis-group includes two known species, Pseudopoda daliensis Jäger & Vedel, 2007 (♂♀), Pseudopoda kunmingensis Sun & Zhang, 2012 (♂♀), and three new species, Pseudopoda anguilliformis sp. nov. (♂♀), Pseudopoda sicyoidea sp. nov. (♂♀), Pseudopoda peronata sp. nov. (♀).